Deliberative Democracy
1 online resource (249 pages)
Keywords: "Deliberative democracy can be seen as a part of the agenda of deepening democracy, wherein the public deliberation of citizens forms the basis of legitimate decision-making, with the people participating directly in the deliberations or making of decisions that affect them. Although political theorists have long contended that democracy should not be based merely on voting but also on informed public debate and despite diverse attempts at deliberative democracy having been made in various parts of the world, it is only during the recent decades that such initiatives have gained momentum.In terms of procedural democracy and the working of democratic institutions, India's record is considered to be noteworthy. However, questions relating to deliberative democracy have come to the fore, particularly in the recent years, with questions of inclusion and equality posing major challenges. The essays in this volume address various dimensions of the issue, ranging from a theoretical conceptualization of deliberative democracy to its role in constitution-making, Gandhian contributions to deliberative democracy, civil society interventions and the role of the media in deliberative processes in India, the participation of new social movements, Dalit and ecological movements, as well as the intricacies of deliberation and decentralization, and issues of development, marginalization and mobilization. The volume facilitates an understanding of the broad contours and evolving nature of democracy in India and how the Indian experience can inform larger debates on deliberative democracy. Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka."--Provided by publisher.